Policy path dependency in a less developed region: The evolution of regional innovation policy in Wales (UK) - Dylan Henderson (Revista Galega de Economía, 2019)
The paper examines the concept of path dependency in policies, and seeks to examine how different pathways emerge in policy and how these change over time. It does so with reference to a case study of regional innovation policy development in Wales (UK) over a period of more than thirty years. Building on recent developments in regional studies and economic geography the paper considers whether path dependency is an inevitable feature of the policy process at the regional level. Drawing on documentary analysis and interviews with policy makers, it finds that policy decisions taken early on in the path creation phase (to support technological innovation) endure despite attempts to broaden out the pathway to a more inclusive form of innovation policy in Wales. While path dependency, most evident in core technological and R&D policy instruments, hasn’t prevented path experimentation, the findings suggest that rigidity and renewal co-exist in policies and the policy process for regional innovation over time. The findings contribute towards the growing focus on the temporal dynamics of policy change at the regional level and the complexity of policy as it seeks to address the challenge of innovation in less developed regions.